Perception of Sexual Education in Institutionalized Adolescents with Lack of Parental Care - Rivera Baylón, Italia; Márquez Vega , María Aracely (Horizonte Sanitario, 2023)
Objective: To identify the perceptions of sexual education in institutionalized adolescents with lack of parental care. Materials and methods: Study with exploratory qualitative approach. Seven interviews were analyzed, three addressed to adolescents with lack of parental care and four to their main caregivers. The MAXQDA Analytics Pro 2020 software was used to interpret the data through content analysis method. Results: The analysis resulted in eight subcategories that were grouped into three large categories: the institutionalized adolescent, perception from the main caregiver and perception of available resources. The results show two possible characteristics of adolescents in this condition, such as the need to be institutionalized due to lack of parental care, as well as the possibility of experiencing traumatic events that have repercussions on adolescent´ health. On the other hand, from the perception of the caregiver, it is observed how the concept of sexuality is constructed, which generally occurs in the school environment or through the exposure of audiovisual elements. On the other hand, there is a lack of recognition of the sexual and reproductive rights of adolescents, as well as the processes of sexual education by main caregivers. Finally, some available resources are identified that can be the basis for strategies development that promote comprehensive sexual education. Conclusion: The analysis of the interviews allow to identify that adolescents in this condition lack an adequate system that will allow them to build a more comprehensive concept of sexuality, remembering that it is not limited to its expression through genitality. Institutions pay special attention to aspects related to social protection such as food, clothing, education, and medical care, however, there are no specific strategies or actions that promote sex education, either due to taboos, fear, or inability to provide it.